Triiodothyronine treatment in mice improves stroke outcome and reduces blood–brain barrier damage - Daniel Ullrich; Dagmar Führer; Heike Heuer; Steffen Mayerl; Steffen Haupeltshofer; Linda-Isabell Schmitt; Markus Leo; Rebecca D Szepanowski; Tim Hagenacker; Markus Schwaninger; Christoph Kleinschnitz; Friederike Langhauser (European Thyroid Journal)
Objective: Thyroid hormones control a variety of processes in the central nervous system and influence its response to different stimuli, such as ischemic stroke. Post-stroke administration of 3,3′,5-triiodo-L-thyronine (T3) has been reported to substantially improve outcomes, but the optimal dosage and time window remain elusive. Methods: Stroke was induced in mice by transient middle cerebral artery occlusion (tMCAO), and T3 was administered at different doses and time points before and after stroke. Results: We demonstrated a dose-dependent protective effect of T3 reducing infarct volumes with an optimal T3 dosage of 25 μg/kg. In addition, we observed a time-dependent effectiveness that was most profound when T3 was administered 1 h after tMCAO (P < 0.001), with a gradual reduction in efficacy at 4.5 h (P = 0.066), and no reduction in infarct volumes when T3 was injected with an 8-h delay (P > 0.999). The protective effect of acute T3 treatment persisted for 72 h post-tMCAO (P < 0.01) and accelerated the recovery of motor function by day 3 (P < 0.05). In-depth investigations further revealed reduced cerebral edema and diminished blood–brain barrier leakage, indicated by reduced extravasation of Evans blue and diminished aquaporin-4 expression. Conclusion: Our findings suggest that T3 may be a promising intervention for ischemic stroke in the acute phase.